Dexamethasone prevents granulocyte-macrophage colonystimulating factor-induced nuclear factor-kB activation, inducible nitric oxide synthase expression and nitric oxide production in a skin dendritic cell line - Vital, Ana Luísa (2003)
AIMS: Nitric oxide (NO) has been increasingly implicated in inflammatory skin diseases, namely in allergic contact dermatitis. In this work, we investigated the effect of dexamethasone on NO production induced by the epidermal cytokine granulocyte / macrophage colony-stimulating factor (GM-CSF) in a mouse fetal skin dendritic cell line.Methods: NO production was assessed by the method of Griess. Expression of the inducible isoform of nitric oxide synthase (iNOS) protein was evaluated by western blot analysis and immunofluorescence microscopy. Western blot analysis was also performed to evaluate cytosolic IkappaB-alpha (IkB-a) protein levels. The electrophoretic mobility shift assay was used to evaluate the activation or inhibition of nuclear factor kappa B (NF-kB).Results: GM-CSF induced iNOS expression and NO production, and activated the transcription factor NF-kB. Dexamethasone inhibited, in a dose-dependent manner, NO production induced by GM-CSF. Addition of dexamethasone to the culture, 30 min before GM-CSF stimulation, significantly inhibited the cellular expression of iNOS. Dexamethasone also inhibited GM-CSF-induced NFkB activation by preventing a significant decrease on the IkB-a protein levels, thus blocking NF-kB migration to the nucleus.Conclusions: The corticosteroid dexamethasone inhibits GM-CSF-induced NF-kB activation, iNOS protein expression and NO production. These results suggest that dexamethasone is a potent inhibitor of intracellular events that are involved on NO synthesis, in skin dendritic cells.